Issues of Teaching English In The Classroom of Heterogeneous Students : A Case Study - Yadav, Ram Ashish; Yadav, Mukesh Kumar (A Bi-annual South Asian Journal of Research & Innovation, 2023)
Issues of teaching English in the classroom of heterogeneous students is a case study. The main purpose of this study is to find the perception of students and teachers towards the heterogeneous class and to publish the data obtained through this research. The narrative research methodology supported with discourse analysis is used as the research methods of this study. Both primary and secondary data are used for this study Interview with individuals, focus group discussion and some classroom observation are used as the data collection tools. 15 teachers and 15 students are the participants of this study. Being Narrative Research, the collected data is analysed descriptively. The conclusion reveals that all the classes are heterogeneous and the teachers have to manage everything tactfully to address the needs of the students and manage the classroom.